Victory for us is to see you suffer in the West Bank with the Palestinians and the Israelis - Winslow, Philip C. (Beacon Press, 2007)
Foreign correspondent Philip C. Winslow captures the human aspects of the [Palestinian] conflict--the daily struggles, desperation, and anger of Palestinian farmers and teachers, the hostility of extremist settlers, the complex range of responses from Israeli soldiers, officials, and peace activists, and even the breathtaking beauty of nature in this embattled place. From these unique multiple perspectives Winslow offers an uncensored view of the realities on the ground that have made a just political solution and enduring peace so difficult.--From publisher description.